Assessment of Development Results - Islamic Republic of Afghanistan - Programme des Nations Unies pour le Développement (United Nations, 2013)
This report presents an independent evaluation managed by the Evaluation Office of the United Nations Development Programme (UNDP) in Afghanistan between 2002 and 2008. It assesses UNDP’s overall contribution to the development of the country over the most recent programming cycles, as well as the strategy and performance of UNDP-Afghanistan during the last programme cycles and their action plans.